HAYDÉE GUANAIS DOURADO FAZ CEM ANOS: APRENDENDO COM A HISTÓRIA - Cristina Maria Meira de Melo; Gilberto Tadeu Reis da Silva; Heloniza Oliveira Gonçalves Costa (Universidade Federal da Bahia, 2015)
EDITORIAL